Study Effect of Cigarette Smoking on the Liver Functions and Electrolytes - Dhahir, Nasir Kareem; Noaman, Aqeel Abbas (Iraqi Journal of Science, 2022)
Smoking have a direct and indirect effects on some organs of the body, this effect is duo to inhaled the smoke and reach the alveoli and in to pulmonary veins. The main objective of this study, to investigate the changes in liver enzymes Alanine aminotransferase(ALT), Aspartate aminotransferase(AST) and Alkaline phosphatase(ALP) and electrolytes like(K+, Na+, Fe+2, Ca+2,Cl- and Po4 -3) in male smokers. In this study collect of (100) blood samples from male smokers and divided in to (3) groups according to period of smoking, and compare with (40) nonsmoker persons (group 4), the age groups are between (25-40) year, in a period between (November 2015-April 2016), within the district of Baqubah in Diyala governorate .The results show increase activity of enzymes ALT, AST and ALP (p<0.001) in smokers compared to control, and no significant differences in the electrolytes (K+, Na+, Cl-) but a significant decrease in Ca+2 level (p<0.001), while the iron concentration increased significantly in all smokers, and the phosphorus concentration increased significantly (p<0.001) in two groups of smokers (10-20) years period of smoking. From this study showed a significant effects on the activity of liver enzymes, Ca+2, Po4-3 and Fe+2in smokers compare to non-smokers while no significant effect on the Sodium, Chloride and Potassium in smokers.